HABILIDADES EMOCIONALES EN HOMBRES Y MUJERES ESTUDIANTES DE CIENCIAS DE LA SALUD - Norma Angélica Ortega Andrade; Karina Duran Ortíz; Guadalupe Arrieta Zúñiga; Ana María Rivera Guerrero; Rubén García Cruz (European Scientific Journal, ESJ, 2013)
Emotional Intelligence (EI) is defined by Salovey and Mayer (1990, Molero, Saiz and Esteban, 1998) that the individual's ability to control one's emotions and those of others as well as to discriminate between them and use the information that you provided, to guide your thoughts and behaviors. For the purposes of this research, emotional intelligence is considered from the model of the "Regulatory Resources" or Emotional Skills Sanchez Aragon (2007, 2010), with the aim of identifying Emotional Skills in Men and Women students Health Sciences, Bachelor of Psychology, Dentistry and Medicine. The study involved 300 students, 100 of a degree in Psychology, 100 Dentistry, and 100 Medicine of the Autonomous University of the State of Hidalgo, Mexico. This sample was selected based on a non-probability sampling type subjects (Garcia, 2009). It is a quantitative, descriptive - comparative with transactional design (Hernández Fernández and Baptista, 2003). We applied the following Battery Tests: Understanding Emotional (PREE), Graphic Battery - Written Emotional Expression and Emotional Perception Test. As for the results obtained from the analysis of Chi Square (X ²), we found no statistically significant differences when comparing each variables (sex and degree), for the three Skills (Understanding Emotional, Emotional Expression and Emotional Perception). We found some statistically significant differences in the interior of the analysis of the variables, results presented below, in order to contribute to the study of the emotional skills in college students.